USING GOOGLE MAPS ASSISTED DRILL METHOD TO IMPROVE LEARNING ACHIEVEMENT AND SELF-CONFIDENCE IN SOCIAL STUDIES SUBJECTS FOR THE 6TH GRADE STUDENTS AT SD NEGERI UNGGULAN MAGETAN REGENCY ACADEMIC YEAR 2019/2020 - Defiliana Wati; Nurhadji Nugraha; Moh Rifa'i (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This research comes from the low percentage of achievement of the 6th Grade student’s Minimum Completion Criteria (MCC) at  SDN Unggulan Magetan. There are 2 of 19 students (10%) passed in the post test on the teaching materials to identify the Continents in the World by using the Drill model learning assisted by Google Maps, and the remaining 17 children were have not passed (90%). These data indicate that the learning outcomes in these teaching materials were incomplete. Therefore, in this case it is necessary to hold classical remedial. The classical remedial process in this case the writer did through classroom action research activities. The objectives of this classroom action research activity are: (1) determining the application of Google maps assisted Drill method in social studies learning; and (2) determining the effectiveness of the application of Google Maps assisted Drill method in social studies learning in order to increase student motivation and achievement. This type of research is the Classroom Action Research with 2 cycles. Each cycle consists of 4 stages, namely: (a) formulation of an action plan, (b) implementation of action, (c) observation, and (4) reflection. Data were obtained through observation, tests, interviews and notes on the results of reflection. Results of the research revealed that (1) the application of the Google Maps assisted Drill method can increase motivation and learning achievement in the social studies subject of the 6th grade student at SDN Unggulan students; and (2) there was improving number of student learning motivation from cycle 1 to cycle 2. In cycle 1 the average score of student learning motivation reached 57.8, while in cycle 2 the average score of student learning motivation reached 78.6. seen from the results of tests conducted by the teacher after completing teaching and learning activities. As initial data or pre-cycle the average value reaches 56, then cycle 1 gets an average value of 64. In cycle 2 the average value reaches 78.